Photographing in the Art Museum: conventions, affordances and projected uses - Stylianou-Lambert, Theopisti (My University, 2016)
While there is a somewhat substantial literature dealing with vernacular, snapshot or else everyday photography, the emphasis is placed on the resulting photographs, their representations and, increasingly, their meaning. There is limited research dealing with the actual act of photographing and the photographic agencies entailed (Larsen, 2008). Nevertheless, the act of photographing is extremely important because it influences, positively or negatively, any lived experience. The proposed research presentation focuses on this almost invisible aspect of everyday photography that is largely understudied: that of the photographic process—the act of taking a photograph and its relationship to experience. To investigate the affordances of photography and the relationship between photography, reproduction and experience, I conducted a research project that examined how visitors use their photographic cameras, smart phones and tablets in an art museum. The research project in discussion used the Smithsonian National Portrait Gallery (in collaboration with the Smithsonian Center for Learning and Digital Access) as a research site. Observation, in-depth interviews with visitors (photographers and non-photographers) and photo-elicitation were used to examine the relationship between art experience and photography. Emphasis was placed not only on the reported potential uses of museum photography, but also on the participants’ movements, interactions, feelings and thoughts during the photographic process. It was assumed from the beginning of the project that semiotic analysis and iconic readings of the resulting photographs could not possibly reveal the meaning processes and photographic experiences of visitors. Since the emphasis of this presentation is on the act of photographing and the meaning of photography, it focuses on theory and research related to (a) the affortances of photographic technologies, and (b) the performativity and embodiment of experiences that the act of photographing invites. When talking about the materiality of photography I’m referring to the fluid materiality of screens (mobile phones, tablets, digital cameras, computers etc.) since all the participants used digital photographic technologies and rarely anticipated that they would print any photographs. In this presentation, in addition to discussing Gibson’s (1979) and Norman’s (1988) “real” and “perceived” affordances, I introduced the concept of “projected” affordances in order to explain what photography does. The data of the research suggest that photography, as a material object, seems to afford a “short-hand” of a layered experience that includes sensory, social, as well as time and space-related information, all of which get embedded in a photograph. This “visual embodiment” of an experience can be potentially reactivated in the future by the photographer, shared with loved ones or instantly shared online with a pool of unidentified users. Nevertheless, even if the photograph is never seen or used in the future, the photograph has “projected affordances”.
Keywords: Affordances; Everyday photography; Art; Museum